Tipologi Rumah-Ladang di Desa Enclave Taman Nasional Bromo Tengger Semeru, Ngadas, Kabupaten Malang - Dian Kartika Santoso; Antariksa Antariksa; Sri Utami (ARSITEKTURA, 2019)
Ngadas village is one of the agricultural villages. Ngadas village was an enclave village of Bromo Tengger Semeru National Park (TNBTS). Ngadas people do more activities in the fields than in their homes or dwellings. So, they built a farmhouse around the crop fields. As an agricultural landscape with upland ecology, certainly there have been many human compositions and interventions in its arrangement. It also changed a shaped of farm houses, and now it has a diverse character. So, it is necessary to study the typology of farmhouses in Ngadas Village as an effort to document traditional architecture and Indonesian culture, especially in the upland agrarian community. Qualitative methods have done with a typology approach by grouping similarities and differences based on the form of plans, unit space, layout, space organization, and orientation. The results of the analysis show that there are five types of farmhouses found. A few factors caused by the emergence of the typology of farmhouses in Ngadas Village based on spatial aspects are topographic factors, economic factors, factors in the need for security.